Peer-coaching interventions for stroke survivors - what works and how: A scoping review - Yichao Chen; Paul Victor Patinadan; Muhammad Amin Shaik; Hui Ling Michelle Chiang; Geraldine Tan-Ho; Farrah Adystyaning Dewanti; Melanie Hui Ru Chng; Andy Hau Yan Ho (PLoS ONE, 2026)
Background Peer-led interventions show potential in supporting stroke survivors’ recovery, but are described using inconsistent terms and definitions in the current literature. Aims Adopting “post-stroke peer-coaching intervention” as the overarching term, this study aims to synthesise the characteristics and outcomes of existing interventions for stroke survivors to develop a standardised definition and a consolidated summary of findings. Summary of review In this scoping review, we searched 6 databases to identify relevant studies from peer-reviewed journal articles published between January 1993 and October 2025. Data were extracted and analysed regarding intervention definitions, characteristics, and outcomes. The search identified 6609 records, and 8 articles were included, which involved 7 post-stroke peer-coaching interventions. An overall inconsistency was observed across intervention definitions and characteristics. Based on common elements across existing interventions, this study developed an integrated definition, describing post-stroke peer-coaching interventions as a time-limited, patient-centred type of psychosocial and psycho-educational intervention that is ideally developed through participatory action research approaches, and delivers informational, emotional, and appraisal support with application of experiential expertise under the guidance of healthcare professionals. The analysis also revealed an inconsistency in intervention outcomes. Conclusion Current post-stroke peer-coaching interventions demonstrated inconsistency across definitions, characteristics, and outcomes. To address the inconsistency, this review established a definition that outlines foundational conceptual parameters of the intervention. This proposed definition can serve as a standardised framework to inform the development of future interventions and ensure the provision of systematic support to individuals with stroke.